DO INVESTORS PREFER NEW OR EXISTING SPONSORSHIP RELATIONSHIPS: EVIDENCE FROM SPONSORSHIP INTERORGANIZATIONAL RELATIONSHIP FORMATION AND MAINTENANCE ON FIRM STOCK RETURNS. Issue 4 (2nd October 2018) - Evans, Robert D.; Deitz, George D.; Sherrell, Daniel L.; Rocco, Richard A.
Abstract : The purpose of this study is to examine investor reaction to the formation of new and the maintenance of existing Interorganizational Relationships (IORs) through the context of official sports sponsorship relationships. Based on a study where the announcements of new and the maintenance of existing sponsorship IORs are disaggregated, it was found that investors reward the formation of new official sponsorship IORs with significant positive abnormal returns to stock price, while returns for the announcement of the maintenance of existing official sponsorship IORs are nonsignificant. Findings suggest investors place a higher premium on the formation of new IORs compared to the maintenance of existing IORs. Implications for the management of IORs are discussed.